Association of functional disability with cardiometabolic disease status in a national cohort study - Ping Ni; Fang Wang; Li Liu; Meiling Ge; Xiuying Hu (Experimental Gerontology)
Background: Cardiometabolic disease (CMD) status increases the risk of functional disability; however, the reverse relationship remains unclear. This study aimed to examine the impact of different patterns of functional disability on CMD status among Chinese middle-aged and older adults. Methods: We used data from two waves of the China Health and Retirement Longitudinal Study. Functional disability was assessed based on activities of daily living (ADL) and instrumental activities of daily living (IADL), while CMD status was evaluated based on the incidence of diabetes, heart disease, and stroke. Generalized ordinal logistic regression analysis was employed to investigate the impact of functional disability on CMD status. Results: In the longitudinal study, 509 individuals (20.0 %) developed CMD, and 102 individuals (4.0 %) developed cardiometabolic multimorbidity. After adjusting for confounders, Model 1 showed an odds ratio of 1.64 (95 % CI: 1.17, 2.29) for increased CMD status in individuals with ADL and IADL disability compared to those without functional disability. Model 2 and Model 3 produced similar results. Conclusions: Functional disability, particularly ADL and IADL disability, increases the risk of CMD status in Chinese middle-aged and older adults. Measures should be implemented to maintain functional status in middle-aged and older adults.